Cisplatin and vinorelbine in the treatment of locally advanced and metastatic non-small cell lung cancer - Wong, Catherine Mee Ming; Lim, Kim Huat; Liam, Chong Kin (Faculty of Medicine, University of Malaya, 2001)
From August 1999 to January 2001, twelve chemotherapy naive patients with locally advanced and metastatic non-small cell lung cancer (NSCLC) in our hospital received vinorelbine and cisplatin. Ten patients had stage IV disease while two had stage III disease. Patients' performance status (PS) were as follows: four had PS 1, six had PS 2, and one each PS 3 and 4. A total of 46 cycles were given as scheduled. Only major haematological toxicities were noted; one patient each with Grade 3 anaemia, Grade 3 and Grade 4 leucopenia, two had Grade 3 neutropenia and 5 had Grade 4 neutropenia without associated mortality. Three patients had Grade 3 alopecia and one had Grade 3 phlebitis.After Three cycles, three patients demonstrated partial response and two had stable disease. For the four patients who completed 6 cycles, two demonstrated stable disease and two partial response. Symptom improvement was reported in all but one patient. Performance status was better in four, stable in six but declined in two patients. in patients with locally advanced and metastatic NSCLC, vinorelbine/cisplatin is a well-tolerated and active regimen, offering symptom palliation and improved performance status in a significant proportion of patients.